A Child with Aarskog Scott Syndrome and Autism Spectrum Disorder - Nur Seda Gülcü Üstün (Sakarya Tıp Dergisi, 2025)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder that is increasingly common in society, characterized by limitations in social communication and some repetitive behaviors. Many genetic factors such as genetic syndromes and single gene mutations and many environmental factors play a role in the etiology of ASD. Many genetic syndromes accompanying ASD have been reported. Aarskog-Scott Syndrome is a rare genetic disorder characterized by facial, digital, and genital anomalies, including a broad upper lip, anteverted nostrils, ptosis, hypertelorism, shawl scrotum, short stature, flat feet, and genu recurvatum. Cases with learning difficulties, hyperactivity, or cognitive retardation have been reported to date with Aarskog Scott syndrome. However, to our knowledge, one case report of ASD and Aarskog Scott syndrome has been reported. In this report, we will present a case with Aarskog Scott syndrome and Autism Spectrum Disorder.